2015
DOI: 10.1128/mcb.01518-14
|View full text |Cite
|
Sign up to set email alerts
|

C1q/Tumor Necrosis Factor-Related Protein 9 Protects against Acute Myocardial Injury through an Adiponectin Receptor I-AMPK-Dependent Mechanism

Abstract: Obesity is a risk factor for cardiovascular disease. C1q/tumor necrosis factor-related protein 9 (CTRP9) is an adipokine that is downregulated by obesity. We investigated the role of CTRP9 in cardiac injury with loss-of-function genetic manipulations and defined the receptor-mediated signaling pathway downstream of this adipokine. CTRP9-knockout (CTRP9-KO) mice at the age of 12 weeks were indistinguishable from wild-type (WT) mice under basal conditions. CTRP9-KO mice had exacerbated contractile left ventricle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 29 publications
8
92
0
1
Order By: Relevance
“…During ischemic injury and proinflammatory stimulation, CTRP9 promotes activation of AMPK and PKA, and both molecules contribute to the protective role of CTRP9 under these circumstances. 14,17,18 During pressure overload, in contrast, we did not find evidence for differential activation of cardiac AMPK or PKA (measured as BAD Ser155 phosphorylation) in response to deletion or overexpression of CTRP9. Instead, we observed enhanced activation of ERK5 during stimulation of isolated cardiomyocytes with recombinant CTRP9 and cardiac AAV-CTRP9 treatment, while in CTRP9 KO mice the induction of ERK5 protein levels in response to pressure overload was markedly blunted compared with what is seen in WT mice.…”
Section: Appari Et Al Ctrp9 Promotes Cardiac Hypertrophy 75mentioning
confidence: 42%
See 2 more Smart Citations
“…During ischemic injury and proinflammatory stimulation, CTRP9 promotes activation of AMPK and PKA, and both molecules contribute to the protective role of CTRP9 under these circumstances. 14,17,18 During pressure overload, in contrast, we did not find evidence for differential activation of cardiac AMPK or PKA (measured as BAD Ser155 phosphorylation) in response to deletion or overexpression of CTRP9. Instead, we observed enhanced activation of ERK5 during stimulation of isolated cardiomyocytes with recombinant CTRP9 and cardiac AAV-CTRP9 treatment, while in CTRP9 KO mice the induction of ERK5 protein levels in response to pressure overload was markedly blunted compared with what is seen in WT mice.…”
Section: Appari Et Al Ctrp9 Promotes Cardiac Hypertrophy 75mentioning
confidence: 42%
“…10,14,15,18 It was demonstrated in these studies that CTRP9 reduces infarct size (by inhibiting cell death) after ischemia/reperfusion injury and that it inhibits adverse remodeling after myocardial infarction. 14,17,18 Although the different disease models per se might play the biggest role to explain these diverse CTRP9 effects, it is possible that in particular pathologically increased endogenous CTRP9 levels (like we observe in mice early after TAC and in hypertrophic human heart disease) are harmful. One should also consider that the protective effects of CTRP9 administration on cardiac remodeling and survival after myocardial infarction were inferred from administration of recombinant globular CTRP9 (lacking large parts at the N-terminal domain), …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CTRP9 also ameliorates left ventricular dysfunction in a mouse model of endotoxemia. 17 In vitro studies showed that CTRP9 attenuates apoptotic activity and inflammatory reaction in cardiac myocytes. 10, 17 The anti-apoptotic and anti-inflammatory effects of CTRP9 in cardiac myocytes are mediated, at least in part, through its ability to promote the AMPK or cyclic AMP signaling pathway.…”
mentioning
confidence: 99%
“…17 In vitro studies showed that CTRP9 attenuates apoptotic activity and inflammatory reaction in cardiac myocytes. 10, 17 The anti-apoptotic and anti-inflammatory effects of CTRP9 in cardiac myocytes are mediated, at least in part, through its ability to promote the AMPK or cyclic AMP signaling pathway. Moreover, CTRP9 improves adverse cardiac remodeling in mice following MI through the PKA-dependent pathway.…”
mentioning
confidence: 99%